23 central composite rotatable design for the production of neem oil nanoemulsion for antifungal and antiparasitic applications. Issue 8 (15th December 2020) - Rabelo, Alessandra S; Sutili, Felipe K; Meneses, Juliana O; Severino, Patricia; Souto, Eliana B; Fujimoto, Rodrigo Y; Cardoso, Juliana C
Abstract: BACKGROUND: The present study describes the design and production of an oil‐in‐water nanoemulsion composed of neem oil as the inner phase for use as an antifungal and antiparasitic control in aquaculture. A 2 3 central composite rotatable design adopting surface response was used as the experimental design, setting the neem oil concentration (4–15%), surfactant concentration (0.5–10%) and sonication power (20–90%) as the independent variables, while the droplet size, polydispersity index (PDI) and zeta potential were set as the response (dependent) variables. RESULTS: Droplet size and PDI showed the best results using the sonication method with 5 min of process. The coefficients of determination were greater than 0.900 for all response. The best formulation was obtained with 9% of neem oil and 5.25% of polysorbate 20. CONCLUSION: Antifungal activity of the optimized nanoemulsion against Saprolegnia parasitica was demonstrated, also attributed to the presence of the surfactant. Concentrations of 200 mg L −1 of nanoemulsion resulted in 100% parasitic mortality. © 2020 Society of Chemical Industry